Adaptive Law in the Era of Disruption: Legal Flexibility in Facing Global Change - Jemielka Roosje Satyana Pilongo; Yohanis Yabes Tjiaman (PT. Anagata Sembagi Education, 2026)
The era of technological disruption marked by the revolution in artificial intelligence, blockchain, the platform economy, and digital transformation has placed conventional legal systems at a critical juncture that requires a fundamental response. This study examines the concept of Adaptive Law as a new legal paradigm that offers flexibility, responsiveness, and regenerative capacity in the face of unprecedented acceleration of global change. Using a normative legal research approach enriched with a comparative analysis of the implementation of adaptive law in various jurisdictions, this study finds that legal systems that are resilient and relevant in the era of disruption are those that integrate continuous renewal mechanisms, regulatory sandboxes, sunset clauses, and multi-stakeholder participation in the norm-formation process. The results of the study indicate that adaptive law is not merely procedural flexibility, but rather a comprehensive legal philosophy that requires a fundamental reconstruction of how the legal system is conceptualized, formed, and implemented. The study's conclusion confirms that the transformation towards adaptive law requires systemic institutional reform, a shift in legislative paradigms, and the development of institutional capacity capable of keeping pace with the increasingly rapid pace of technological and social change.